2021
DOI: 10.3389/fendo.2021.794623
|View full text |Cite
|
Sign up to set email alerts
|

The Uptake of Ethinyl-Estradiol and Cortisol From Water by Mussels (Mytilus spp.)

Abstract: Previous toxicokinetic studies have shown that mussels (Mytilus spp.) can readily absorb the three main mammalian sex steroids, estradiol (E2), testosterone (T) and progesterone (P) from water. They also have a strong ability to store E2 and the 5α-reduced metabolites of T and P in the form of fatty acid esters. These esters were shown to have half-lives that were measured in weeks (i.e. they were not subject to fast depuration). The present study looked at the toxicokinetic profile of two other common steroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Extraction and phase separation of the metabolites in the snail tissues showed the presence of a high proportion of radioactivity (40, 50 and 85%) for P, E 2 , and T, respectively, in the lipid-rich heptane fraction where esterified steroids would be expected to accumulate ( Figure 2 ). The proportion of EE 2 that had been potentially esterified was, as expected ( 18 ), much lower (8%). Most of the rest of the radioactivity was recovered in the 80% ethanol fraction which contains free steroids.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Extraction and phase separation of the metabolites in the snail tissues showed the presence of a high proportion of radioactivity (40, 50 and 85%) for P, E 2 , and T, respectively, in the lipid-rich heptane fraction where esterified steroids would be expected to accumulate ( Figure 2 ). The proportion of EE 2 that had been potentially esterified was, as expected ( 18 ), much lower (8%). Most of the rest of the radioactivity was recovered in the 80% ethanol fraction which contains free steroids.…”
Section: Resultssupporting
confidence: 74%
“…We confirmed that snails do indeed, like many other mollusks, absorb vertebrate steroids. Compared to M. edulis ( 15 18 ), the rate was approximately ten times slower on a per animal basis. On a gram for gram basis, however, the difference was c .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Since no live animal studies have been carried out under immaculate steroid-free conditions (humans are a substantial potential source of contamination in laboratories) (11), it is impossible to know for sure whether a steroid level has changed because that is what it should have done if it really was a hormone, or because there was increased contamination, or a reduction in esterification, or an increase in de-esterification [or at least fourteen other potential mechanisms that could produce the same results (12)]. In fact, uptake and esterification of steroids by marine mollusks were firmly demonstrated in 2001 (57) and have since been confirmed many times by investigating different marine molluscan species (26,31,(58)(59)(60)(61)(62). Yet publications that make no mention of these mechanisms continue to appear in the literature.…”
Section: On the Way To The Light: Uptake And Esterification Of Steroi...mentioning
confidence: 99%